The Analysis of Islamic Religious Education Learning Methods from Imam Al-Ghazali's Perspective on Students with Special Needs at MA Darun Najah - Machnunah Ani Zulfah; Muhamad Lutfi (SCHOOLAR: Social and Literature Study in Education, 2024)
In general, the purpose of this study was to determine the learning method of Islamic religious education according to Imam Al-Ghazali in inclusive students. The benefit of this research is to improve the learning of inclusive students by using the Imam al-Ghazali perspective learning method. This study uses a qualitative descriptive method with interview, observation and documentation techniques. Data processing is done by giving meaning to the data that has been collected and analyzed in a qualitative description, then conclusions are drawn. The results of this study show that al-Ghazali's thoughts on learning methods of Islamic religious education for inclusive students are 1) the mujahadah and riyadhoh-nafsiyah able to help educators in the learning process for inclusive students at MA Darun Najah, one of the factors that emphasizes students' thinking processes diligently. so that it leaves a good impression on the students' souls and will really pursue it, 2) one of the inhibiting factors is that the level of focus is not like normal children in general so that sometimes they lack focus when receiving lessons, pay less attention when the learning process takes place and there is even a sense of lazy and not even in the mood or have no desire to learn, and 3) the supporting factors are parents, family and the methods used by the teacher in the learning process.